The effect of irrigation and nitrogen fertilization on the soybean seed yield, with a correlation to the protein and oil concentration - Galić Subašić, Daria; Jurišić, Mladen; Jug, Irena; Josipović, Marko, agronom; Kiš, Darko; Rapčan, Irena (2020)
The paper presents the result of a triennial field experiment (2013‒15), aiming to determine the influence of irrigation, nitrogen fertilization, and cultivars, as well as their interactions on the yield and chemical properties of the soybean seeds. Four soybean cultivars (Lucija, Vita, Ika and Tena) of different maturity groups were investigate as a sub‐subplot factor (C). The main plot factor (A - irrigation) resulted in a statistically very significant (P≤0.01) seed yield in all three years, and it was found out by an analysis of variance. The subplot factor (B - nitrogen fertilization) had an impact on the grain yield depending on the research year, while sub‐subplot factor (C-cultivar) significantly affected all examined traits. The factor interactions and their significance varied by the research years. The seed yield achieved in 2013 (3883 kg ha-1) indicated a great importance of all factors’ interaction. The correlations between a seed yield and a protein and oil concentration were determined during the research.
U radu su prikazani rezultati trogodišnjih poljskih pokusa (2013. – 2015.), s ciljem utvrđivanja utjecaja navodnjavanja, gnojidbe dušikom i sorte te njihove interakcije na prinos i kemijska svojstva zrna soje. Ispitivane su četiri sorte soje (Lucija, Vita, Ika i Tena) različitih grupa zriobe kao pod‐podčimbenik (C). Analizom varijance utvrđeno je da se glavni čimbenik (A – navodnjavanje) statistički vrlo značajno (P≤0,01) odrazio na prinos zrna u svima trima godinama. Podčimbenik (B – gnojidba dušikom) imao je utjecaja na prinos zrna zavisno o godini istraživanja, dok je pod‐podčimbenik (C – sorta) značajno utjecao na sva ispitivana svojstva. Interakcije čimbenika i njihova značajnost razlikovale su se prema godini istraživanja. Ostvareni prinos zrna u 2013. godini (3883 kg ha-1) ukazuje na veliko značenje međusobnoga djelovanja svih čimbenika. Tijekom istraživanja utvrđene su korelacije između prinosa sjemena i koncentracije bjelančevina i ulja.
Bibliografija: 33 jed.
Summary ; Sažetak.
Keywords: Soja -- Navodnjavanje -- Gnojidba dušikom -- Sorte -- Prinos sjemena